2020
DOI: 10.1080/09712119.2020.1830779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein supplements on fertility and assessment of the fertility genes (GDF9andBMP15) in indigenous sheep of Bangladesh

Abstract: The study was conducted to investigate the effect of different levels of protein supplements on fertility and assess the fertility gene (BMP15 and GDP9) in sheep of Bangladesh. Thirty six ewes fed two protein level (Treatment 1, T1 and treatment 2, T2) and no protein supplement ration (control, T0). Polymerase chain reactions (PCR) were performed from blood cell DNA following standard protocols. PCR products were sequenced using Sanger sequencing and MEGA6 software were used for molecular analysis. The concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
2
2
1
Order By: Relevance
“…However, sequence alignment showed four other selected mutations in GDF9 [c.260G>A (FecG1) and c.1184C>T (FecG8)] and BMP15 [c.69C>T (FecX G and c.718C>T (FecX HIL )] gene fragments were monomorphic in the studied populations that limits for further PCR-RFLP genotyping. Similar to the present findings, Hossain et al (2020) reported the absence of polymorphisms in BMP15 and GDF9 genes of indigenous sheep of Bangladesh. This finding partially agrees with the results of Roy et al (2011) who reported all considered loci of BMP15 and GDF9 genes were monomorphic except two (G1 and G4) of GDF9 were found to be polymorphic in Indian Bonpala sheep.…”
Section: Resultssupporting
confidence: 91%
“…However, sequence alignment showed four other selected mutations in GDF9 [c.260G>A (FecG1) and c.1184C>T (FecG8)] and BMP15 [c.69C>T (FecX G and c.718C>T (FecX HIL )] gene fragments were monomorphic in the studied populations that limits for further PCR-RFLP genotyping. Similar to the present findings, Hossain et al (2020) reported the absence of polymorphisms in BMP15 and GDF9 genes of indigenous sheep of Bangladesh. This finding partially agrees with the results of Roy et al (2011) who reported all considered loci of BMP15 and GDF9 genes were monomorphic except two (G1 and G4) of GDF9 were found to be polymorphic in Indian Bonpala sheep.…”
Section: Resultssupporting
confidence: 91%
“…Parity order affected significantly the reproductive parameters, old ewes positively showed higher conception and lambing rate, this finding was similar to the other researcher results [10,11,22,23,43,44] and [34] demonstrated that they increasing the age of ewes could increase the pregnancy rate and multiple births, also [26] reported that ewe age significantly affected both the pregnancy and lambing rates, primiparous ewes had a higher lambing rate (72.0%) than that (44.2%) of multiparous ewes, and he concluded that old aged ewes had a less conception rate than 1 to 2 years aged ewes. Also [43] reported that the fertility rate was lower in 1.5-year-old ewes than in older ewes.…”
Section: Effect Of Supplementation Strategies and Parity Order On Rep...supporting
confidence: 90%
“…Also agreed with [58] he demonstrated that increase in reproductive rate in supplemented ewes was due to increases in both conception rate and fecundity, with a higher proportion of pregnant ewes, and a higher proportion of multiple pregnancies, in the supplemented groups. Contrast to these results [34] reported that the number of fetuses per ewe pregnant was not influenced by level of nutrition. Results in this study showed that ewes depend on natural grazing alone scored lower litter size, similar result obtained by [59] who stated explained lower litter size in terms of the scarcity and low quality of the forage in the tropical rangelands, which are subject to uncertain seasonal rainfall patterns, and where supplemental feed is also scarce and economically unfeasible.…”
Section: Effect Of Supplementation Strategies and Parity Order On Lit...contrasting
confidence: 77%
See 1 more Smart Citation
“…Table 3 shows the variations of the post-partum intervals of Bangladeshi indigenous and exotic cross breeds sheep under reviewed works. Hossain et al, (2020) AFS-Age at first service, GL-Gestation length, AFL-Age at first lambing, LI-Lambing interval, PPI-Post-partum interval,…”
Section: Post-partum Intervalmentioning
confidence: 99%